Retracted: Management and overview of postoperative chylothorax after congenital cardiothoracic surgery - Bansal, Dhananjay; Chugh, Vaibhav; Bhushan, Rahul; Banday, Javed M.; Jhajhria, Narender S.; Grover, Vijay; Gupta, Vijay K. (International Surgery Journal, 2019)
The article " Management and overview of postoperative chylothorax after congenital cardiothoracic surgery " is retracted by the Editor-in-Chief, on the request of corresponding author and co-authors who informed errors in data collection after departmental review and post hoc analysis. The article is retracted because the results may be affected due to the errors.